New Testament exegesis in theory and practice: the various stages of the exegetical programme - A. B. du Toit (Acta Theologica)
The various stages in the exegetical programme include preliminary selection of a passage, first close reading, demarcation, textual criticism, determining the real world context, the literary type, the place of the micro-text within its macro-structure, analysing the structure of the micro-text, detailed analysis, formulating the message for the first readers, guidelines for understanding the text’s message for today and (optional) a translation. Lexico-grammatical, literary and semantic criteria for text demarcation are presented. Under detailed analysis a new linguistic tools, metaphors, Semitic influence and intertextuality are discussed.